Parâmetros interpretativos do Supremo Tribunal Federal na solução de colisões entre o direito fundamental ao meio ambiente e o princípio da livre iniciativa - Nepomuceno, Taiane Maciel (My University, 2025)
This dissertation investigates the interpretative parameters adopted by the Supreme Federal Court (STF) to resolve conflicts between the right to an ecologically balanced environment (Art. 225, Federal Constitution of 1988) and the objective principle of free enterprise (Arts. 1, IV, and 170, Federal Constitution of 1988). Initially, the definitions, contents, and scope of these constitutional rights are presented, highlighting the interdependence between economic development and environmental sustainability and reinforcing the need for their harmonization. The dissertation then moves on to examine the interpretative parameters applicable to conflicts between fundamental rights and the instrumental principles of constitutional interpretation, which form the theoretical basis for this case-law review. Methodologically, this is a qualitative, theoretical-empirical, and analytical-jurisprudential study, supported by structured proportionality (Robert Alexy) - adequacy, necessity, and proportionality in the strict sense, the law of collision, weighing structures, and prima facie priorities - and integrity (Ronald Dworkin), which requires principled decisions, systemic coherence, and intergenerational responsibility. Using Toni M. Fine's method for case reading, RE 134,297/SP, ADI 3,540-MC/DF, ADPF 101/DF, RE 607,109/PR, and ADI 6,218/RS are analyzed. The results show: a) conditional prevalence of environmental protection when relevant risks are demonstrated and the adequacy and indispensability tests are met (partial confirmation of the hypothesis of preference under art. 225); b) consistent use of proportionality as a compatibility technique (confirmation of the methodological hypothesis); c) affirmation of the prohibition of insufficient protection, non-regressivity, and the possibility of more protective local regimes; and d) recognition of an institutional factor - the seriatim model of deliberation - that demands greater discipline in reasoning to ensure intersubjective control. It is concluded that the STF consolidates a jurisprudential model of sustainable development, conditioning free enterprise to sustainability standards under a combined matrix of proportionality and integrity. [resumo fornecido pelo autor]
A dissertação investiga quais parâmetros interpretativos o Supremo Tribunal Federal (STF) adota para solucionar colisões entre o direito ao meio ambiente ecologicamente equilibrado (art. 225, CF/88) e o princípio objetivo da livre iniciativa (arts. 1º, IV, e 170, CF/88). Inicialmente, apresentam-se as definições, os conteúdos e o alcance desses bens constitucionais, destacando a interdependência entre desenvolvimento econômico e sustentabilidade ambiental e reforçando a necessidade de sua harmonização. Em seguida, passa-se ao estudo dos parâmetros interpretativos aplicáveis às colisões entre direitos fundamentais e dos princípios instrumentais de interpretação constitucional, que compõem a base teórica do exame jurisprudencial. Metodologicamente, realiza-se estudo qualitativo, teórico-empírico e analítico-jurisprudencial, apoiado na proporcionalidade estruturada (Robert Alexy) ? adequação, necessidade e proporcionalidade em sentido estrito, lei da colisão, estruturas da ponderação e prioridades prima facie - e na integridade (Ronald Dworkin), que exige decisões por princípio, coerência sistêmica e responsabilidade intergeracional. A partir do método de Toni M. Fine para leitura de casos, analisam-se o RE 134.297/SP, a ADI 3.540-MC/DF, a ADPF 101/DF, o RE 607.109/PR e a ADI 6.218/RS. Os resultados mostram: a) prevalência condicionada da tutela ambiental quando demonstrados riscos relevantes e superados os testes de adequação e indispensabilidade (confirmação parcial da hipótese de preferência pelo art. 225); b) uso consistente da proporcionalidade como técnica de compatibilização (confirmação da hipótese metodológica); c) afirmação da vedação de proteção insuficiente, da não-regressividade e da possibilidade de regimes locais mais protetivos; e d) reconhecimento de um fator institucional - o modelo seriatim de deliberação - que demanda maior disciplina de fundamentação para garantir controlabilidade intersubjetiva. Conclui-se que o STF consolida um modelo jurisprudencial de desenvolvimento sustentável, condicionando a livre iniciativa a padrões de sustentabilidade sob uma matriz combinada de proporcionalidade e integridade. [resumo fornecido pelo autor]
Keywords: Direitos fundamentais; Meio ambiente; Brasil. Supremo Tribunal Federal; Civil rights; Environment; Brazil. Federal Supreme Court